2010
DOI: 10.1097/hcr.0b013e3181d0c493
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Fatigue Associated With Acute Myocardial Infarction

Abstract: INTRODUCTION Fatigue is a symptom of acute myocardial infarction (AMI); however, few studies have characterized the fatigue associated with AMI in men and women. METHODS The convenience sample included 88 men and 28 women admitted with a diagnosis of AMI at 6 Midwestern facilities. Data were collected upon hospital admission and 30 days after discharge. A total of 37 men and 10 women responded to the 30-day questionnaires. The Profile of Mood States Fatigue (POMS-F) subscale was used to measure fatigue and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
11
1
1
Order By: Relevance
“…Earlier studies have found that men and women differ in their experiences of fatigue 30 days after MI, such that fatigue was a much greater issue for women than for men (Fennessy et al . ). Five years after MI, women experienced fatigue as one of the most common symptoms leading to limitations in their lives (Sjostrom‐Strand et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier studies have found that men and women differ in their experiences of fatigue 30 days after MI, such that fatigue was a much greater issue for women than for men (Fennessy et al . ). Five years after MI, women experienced fatigue as one of the most common symptoms leading to limitations in their lives (Sjostrom‐Strand et al .…”
Section: Discussionmentioning
confidence: 97%
“…Although there is a close relationship between fatigue and depression after MI (Fennessy et al . ), it has also been shown that symptoms of fatigue can occur without coexisting depression after MI (McGowan et al . ).…”
Section: Introductionmentioning
confidence: 98%
“…Trajectories of both fatigue and vital exhaustion have been identified in ACS patients after discharge (Fennessy et al, 2010; Smith, Kupper, Denollet, & de Jonge, 2011). Different symptom trajectories have been associated with differences in disease-related outcomes: Severe and increasing vital exhaustion trajectories have been associated with a greater incidence of cardiac events than mild and decreasing trajectories in one study using latent class growth analysis (Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Different symptom trajectories have been associated with differences in disease-related outcomes: Severe and increasing vital exhaustion trajectories have been associated with a greater incidence of cardiac events than mild and decreasing trajectories in one study using latent class growth analysis (Smith et al, 2011). In another study using regression analysis, symptom trajectories also varied by sex, with women often experiencing severe but improving fatigue, in contrast to men’s moderate, persistent fatigue (Fennessy et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as many as 50 percent of patients have been found to report fatigue four months after a myocardial infarction [16]. Experiences of illness-related fatigue include feelings of tiredness, weakness and lack of energy, and consequently, fatigue is closely related to depression after myocardial infarction [17]. Depressed people primarily experience fatigue, as fatigue is a key symptom of depression [18].…”
Section: Introductionmentioning
confidence: 99%